Atlanta's Potential Immigrant Voters: Where Are They, Who Are They, and How Is Their English? - Charles Jaret (Journal of Public and Professional Sociology, 2017)
This paper gives a profile of immigrants (especially those who are naturalized U.S. citizens) living in metropolitan Atlanta’s five core counties (Clayton, Cobb, DeKalb, Fulton, and Gwinnett) plus Hall County (an area that has a relatively high percentage of foreign-born residents). Information on these potential immigrant voters comes from the U.S. Census Bureau’s 2010-2014 American Community Survey five-year estimate data tables accessed via Social Explorer. Some important or surprising findings are that very few potential immigrant voters live within the boundaries of the City of Atlanta, there are more female than male potential immigrant voters, there are almost twice as many Asian potential immigrant voters than Latino potential immigrant voters, and no region-of-origin group forms a majority of potential immigrant voters. Data confirm that Gwinnett County has the largest percentage of potential immigrant voters and show that households of Korean and Vietnamese background are lowest in English proficiency. Immigrants in metro Atlanta who have been elected to office are identified and 2016 election results for immigrant candidates for office are provided. Also, political implications of Atlanta’s immigrant voters are discussed.